More lawyers, more litigation? - Avner Levin; Asher Alkoby (Oñati Socio-Legal Series)
This brief paper explores the correlation and potential relationship between the composition of the legal profession and trends in litigation, in Ontario, Canada. Specifically, we ask whether there is a positive correlation between the numbers of lawyers and paralegals licensed to practice in the province, and the amount of civil litigation initiated across the province. The paper then discusses possible reasons for the trends in the profession and in litigation, and considers traditional objections, such as the argument that an increase in the number of lawyers will lead to 'litigation explosion'. The paper concludes with suggestions for future research in this area.